The Development of an Instrument for Client Based Principal Evaluation - Howard Ebmeier; Alfred Wilson (Educational Considerations, 1989)
Given the shortcomings of existing administrator evaluation instruments and in particular of those of a diagnostic nature, it is desirable to design a sound measurement instrument that can be used with confidence by practitioners. (Program Approaches to Administrative Training and Development.)